Etos Khidmah Dalam Pesantren Salaf: : Kajian Atas Proses Pembentukan Karakter Khidmah Di Pondok Pesantren Langitan Widang Tuban - Muhammad Najib; Achmad Miftachul Fawwaz (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2025)
Abstract Purpose: This study aims to explain the formation process of khidmah character at Pondok Pesantren Langitan Widang Tuban, a traditional Islamic boarding school that consistently maintains devotional values in its educational system. Design/methodology/approach: This research employs a qualitative phenomenological approach with data collection through observation, in-depth interviews, and documentation to understand the lived experiences of santri (students) and teachers in developing khidmah character. Research limitations/implications: This study is limited to one pesantren context. However, it provides valuable insights for character education development in Islamic educational institutions and offers an alternative model for contemporary education systems facing moral crisis. Findings: The results reveal three main stages in khidmah character formation: knowledge transfer through teacher exemplification, habituation of khidmah values in daily life, and embodiment of khidmah character in real acts of service to the pesantren and community. The process demonstrates that character education involves not only teaching values but also consistent practice. Originality/value: This research contributes to character education literature by documenting a proven traditional Islamic educational approach that integrates spiritual, moral, and social dimensions in character formation, which can serve as a model for other educational institutions.